Trend Analysis of Autumn Rainfall Averages in Misurata, Northwestern Libya during the Period (1960–2023) (Journal of Libya for geographical studies, 2026)
This study aims to analyze trends in autumn rainfall averages in Misurata, northwestern Libya, during the period 1960–2023, based on climatic data from the Misurata Meteorological Station. Statistical methods commonly used in climate trend analysis were applied, including moving averages, cumulated sums (CUSUM), simple linear regression, and the t-test. The results indicate a general decreasing trend in autumn rainfall averages over the study period, particularly toward the year 2023. Additionally, the study found that 57.81% of autumn seasons during the period were classified as dry, with average rainfall below the long-term mean for the region. These findings highlight a clear pattern of rainfall reduction in autumn, which has important implications for water resources management and planning in Misrata and the surrounding areas.
Keywords: Misurata; Autumn rainfall; Simple linear regression; Trend analysis